Pengaruh Kebijakan Kompensasi dan Pengembangan Karir Terhadap Retensi Karyawan Generasi Z - Rizki, Via Lailatur; Fitria, Novy; Muttaqien, Fauzan (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
This study aims to analyze the influence of compensation policies and career development on the retention of Generation Z employees. Generation Z, born between 1995 and 2010, has unique characteristics in terms of work preferences and motivation. This research employs a quantitative method by distributing questionnaires to 257 Generation Z employees in various companies in Indonesia. The obtained data were analyzed using multiple linear regression. The analysis results show that compensation policies (β = 0.35, p < 0.01) and career development (β = 0.42, p < 0.01) significantly influence Generation Z employee retention. Fair and competitive compensation policies and clear, structured career development programs have been proven to increase employees' desire to stay with the company. The Adjusted R-squared value of 0.58 indicates that this model explains 58% of the variation in employee retention. This study provides practical implications for company management in designing compensation policy and career development strategies to enhance employee retention, especially among Generation Z.